KEPUASAN PESERTA TERHADAP KUALITI PENYAMPAIAN MAKLUMAT PENGURUSAN PEWARISAN ISLAM: KAJIAN KE ATAS AKTIVITI PROGRAM BAITULMAL MAJLIS AGAMA ISLAM SELANGOR (MAIS): Participant Satisfaction With The Quality of Information Delivery on Islamic Inheritance Management: A Study on The Activities of Baitulmal Majlis Agama Islam Selangor (MAIS) - Lazib, Ihyaul; Madun, Azian (Online Journal of Islamic Management and Finance (OJIMF), 2025)
The principles of Islamic inheritance have been clearly outlined in the primary sources of Shariah, namely the Quran, Hadith, Ijma’, and Qiyas, along with structured procedures for estate management. However, the Muslim community still faces challenges in understanding and implementing inheritance distribution due to limited knowledge of faraid (Islamic inheritance law), hibah (gifts), wasiat (wills), and the processes involved in estate claims. To address these issues, Baitulmal MAIS has initiated various educational programs, including seminars, courses, and advisory services, to enhance public awareness. This study aims to evaluate the quality of information delivery in Islamic estate management programs organized by Baitulmal MAIS and assess participants' satisfaction with these programs. The SERVQUAL model was applied to measure service quality across five key dimensions: reliability, assurance, responsiveness, empathy, and tangibles. This study adopted a quantitative approach using questionnaires distributed to participants at three faraid programs held at different locations. The sample was selected through convenience sampling, involving 97 respondents out of 200 participants, representing a response rate of 48.5%. The findings indicate that all SERVQUAL dimensions positively influence participant satisfaction. The "tangibles" dimension recorded the highest score, while "reliability" scored the lowest. The study recommends extending program durations, conducting follow-up programs, and improving delivery methods to enhance the effectiveness of Islamic inheritance education.